Analysis of therapeutic effects of congenital kyphosis in children due to anterior vertebral bone bridges - Xu, Ke; Zhang, Cefei; Xia, Bing; Zhao, Yufeng; Jiang, Xiaowei; Li, Chonghao; Hu, Weiming; Liu, Fuyun (Frontiers in Surgery, 2024)
Objective To investigate the choice of treatment options and long-term orthopedic results of congenital kyphosis in children due to anterior vertebral bone bridges. Methods The clinical data of children with congenital kyphosis due to anterior vertebral bridges treated at our center from May 2005 to May 2020 were retrospectively analyzed. We evaluated the clinical features of the deformity, the choice of treatment plan, the change in the Cobb angle of the kyphosis and the improvement of the sagittal trunk deviation before and after treatment and at the final follow-up visit by means of pre-treatment and post-treatment imaging, physical examination and analysis of the case data. Results A total of 35 children were included. Clinical follow-up was conducted on a cohort of 5 children, all of whom presented with type Ⅱ congenital kyphosis caused by less than three thoracic anterior bone bridges. The study findings revealed no noteworthy advancement in segmental kyphosis, thoracic kyphosis, lumbar lordosis, and sagittal vertical axis during the final follow-up assessment (p > 0.05). In a cohort of 30 pediatric patients who underwent surgical intervention, segmental kyphosis was corrected, with a decrease from an average angle of (40.1 ± 20.5)° to (15.6 ± 9.5)°. Furthermore, significant improvements were noted in segmental kyphosis, thoracic kyphosis, lumbar lordosis, and sagittal vertical axis at the postoperative stage compared to the preoperative stage (p < 0.05). Notably, improvements in thoracic kyphosis and lumbar lordosis persisted at the final follow-up visit compared to postoperative (p < 0.05). Conclusion Type Ⅱ congenital kyphosis in children caused by anterior bony bridges of less than three vertebrae in the thoracic segment can be followed up for a long period, and type Ⅱ/Ⅲ congenital kyphosis caused by anterior bony bridges of the vertebrae in the thoracolumbar, lumbar, and lumbosacral segments requires early surgery.